Content of total forms of heavy metals in some soil types formed on marl - Andreevski, Marjan; Hristovski, Slavčo; Popovska, Hristina; Mukaetov, Duško (Macedonian Journal of Ecology and Environment, 2010)
The main goal of these investigations is to determine the total content of heavy metals (Pb, Cd, Cr, Ni and Co) in regosols and rendzinas formed on marl. An area of 11 ha was examined with excavation of two soil profiles, one regosol (prof. 1) and one rendzina soil profile (prof. 2) in the vicinity of village Timjanik (city of Negotino), Cucka locality. Soil samples were digested with “aqua regia” (1:3 ratio of concentrate HCl and HNO3 ). Determination of Cr and Ni was performed on atomic emission spectrometer with inductively couplet plasma Varian 715 ES, while Cd, Co and Pb with electrothermal atomic absorption spectrometer Varian 614 Z. The content of total lead and cadmium is lower than the referent values, while the content of total chromium and cobalt in some soil samples is a bit higher than the referent values. The content of total nickel is higher than the referent values, but less than the intervene values, except in the hor. Ap of prof. 2 where the content of total nickel was higher than the intervene values.